The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1258/acb.2010.090305
|View full text |Cite
|
Sign up to set email alerts
|

The increased plasma C-reactive protein and interleukin-6 levels in patients undergoing coronary artery bypass grafting surgery are associated with the interleukin-6−174G > C gene polymorphism

Abstract: Background: The interleukin-6 (IL-6) promoter 2174G/C polymorphism (rs1800795) is associated with enhanced systemic inflammatory response to injury. However, data on the effect of this polymorphism on inflammatory markers in patients undergoing coronary artery bypass grafting surgery (CABG) are inconsistent. The aim of our study was to investigate whether 2174G/C IL-6 polymorphism affects plasma IL-6 and C-reactive protein (CRP) concentrations in patients undergoing CABG. Methods: A total of 179 consecutive wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 28 publications
3
18
1
3
Order By: Relevance
“…The 2174 G/C polymorphism is a common variant that regulates the serum concentration of IL-6 (22-28). In keeping with previous studies in patients with CVD (28), coronary artery bypass grafting surgery (23,25), carotid atherosclerosis (24), abdominal aortic aneurysm (22), and dialysis (26), we found that patients with CKD and CC genotype had higher circulating levels of IL-6 and CRP than those harboring GC or GG genotypes, specifically legitimating the use of this genetic marker as an unbiased means for assessing the causal nature of the link between the gene product (IL-6) of this polymorphism and CV complications in CKD. Interestingly, this analysis showed that this polymorphism is independently associated both with the history of CVD as well as with incident CV events.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The 2174 G/C polymorphism is a common variant that regulates the serum concentration of IL-6 (22-28). In keeping with previous studies in patients with CVD (28), coronary artery bypass grafting surgery (23,25), carotid atherosclerosis (24), abdominal aortic aneurysm (22), and dialysis (26), we found that patients with CKD and CC genotype had higher circulating levels of IL-6 and CRP than those harboring GC or GG genotypes, specifically legitimating the use of this genetic marker as an unbiased means for assessing the causal nature of the link between the gene product (IL-6) of this polymorphism and CV complications in CKD. Interestingly, this analysis showed that this polymorphism is independently associated both with the history of CVD as well as with incident CV events.…”
Section: Discussionsupporting
confidence: 76%
“…Because transmission of genes is a random phenomenon, gene polymorphisms modulating IL-6 synthesis may represent an unbiased means for testing whether the link between IL-6 and CV outcomes in patients with CKD is causal (Mendelian randomization). The 2174 G/C single-nucleotide polymorphism is a functional variant located in the promoter region of the IL-6 gene that regulates the rate of IL-6 gene transcription (22)(23)(24)(25)(26)(27)(28) and therefore represents a reliable research tool for testing the nature (causal versus noncausal) of the link between IL-6 and CV outcomes in CKD. With this background in mind, we set out to confirm findings by Barreto et al (21) in a large observational study with a carefully characterized cohort of 755 patients with stages 2-5 CKD and to test whether this relationship may underlie a causal link by applying the Mendelian randomization approach (i.e., by stratifying the study population according to the functional 2174 G/C polymorphism in the IL-6 gene).…”
Section: Introductionmentioning
confidence: 99%
“…Кроме того, некоторые генетические полимор-физмы и внешние факторы могут играть роль в увели-чении восприимчивости организма к развитию ФП [4]. Данные литературы свидетельствуют о значимости кли-нических и генетических параметров в инициировании послеоперационной ФП (ПОФП) [3,5].…”
unclassified
“…Функциональный полиморфизм в промоторной области IL-6 C174G связан с повышением риска раз-вития ишемической болезни сердца (ИБС) [5]. IL-6, синтезированный в ответ на различные триггеры, способствует воспалительному процессу.…”
unclassified
See 1 more Smart Citation